2011
DOI: 10.1111/j.1468-0432.2011.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Gender Equality without a Gender Perspective: Problem Representations of Equal Pay in Finland

Abstract: The current locus of promoting equal pay in Finland is the workplace. Legal instruments, like gender equality planning and its pay surveys, are to be implemented in workplaces. This development raises important questions about the central role of the local trade union representatives as promoters of equal pay. This article analyses how local trade union representatives construct the problem of unequal pay and their role in narrowing the gender pay gap and their possible agonistic adversaries in negotiations on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(60 citation statements)
references
References 14 publications
1
49
0
6
Order By: Relevance
“…This often becomes gender blindness. Milja Saari (2013) has analyzed how local trade union representatives construct the problem of unequal pay. She found that not only was the wage-bargaining culture gender neutral, but gender neutrality was also regarded as a value in itself.…”
Section: Tensions In Gender Mainstreamingmentioning
confidence: 99%
“…This often becomes gender blindness. Milja Saari (2013) has analyzed how local trade union representatives construct the problem of unequal pay. She found that not only was the wage-bargaining culture gender neutral, but gender neutrality was also regarded as a value in itself.…”
Section: Tensions In Gender Mainstreamingmentioning
confidence: 99%
“…Given that women are more likely to be low paid (Saari 2013;Warren, 2003), we see a higher proportion of women being excluded (Meyer, 2014). However, even for those enrolled there are concerns that the value of the pension will not to deliver sustainable retirement incomes (PWC, 2012;Uren 2013).…”
Section: Gender Blindness and Auto-enrolmentmentioning
confidence: 96%
“…Since then there have been excellent analyses and critiques of discrimination and policy (Ainsworth et al 2010;Colley, 2003Colley, , 2013Duncan and Loretto 2004;Woodward and Winter, 2006), much of which has been published in Gender Work and Organization and by advocacy groups (such as the Fawcett Society 2007;Working Families, 2010). We have also seen the proliferation of impressive work addressing gender blindness in organization studies (Benokraitis and Feagin, 1995;Husu, 2001;Kantola, 2006Kantola, , 2008Lindvert, 2002;Saari, 2013;) that keep women in disadvantaged positions, and also critiques of how various pension policy reforms have impacted on women disproportionately (Fredericks, 2007;Green, 2005;Leitner, 2001;Loretto and Vickerstaff, 2013;Marier, 2007: Peinado, 2014Sefton et al, 2011;Vara, 2013).…”
Section: Exploring Gender Blindness and Heteropatriarchymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Finland, the idea of equality is included in the Constitution (731/1999), where equality of the sexes is said to be "promoted in societal activity and working life, especially in the determination of pay and the other terms of employment, as provided in more detail by an Act." However, although Finland, like other Nordic countries, is regarded as one of the most gender-equal countries in the world there are still very strong gender equality problems in the Nordic country, especially in relation to gender pay gap, amongst others (Saari, 2011).…”
Section: 《宪法》规定我国公民的基本权利,主要包括以下几个方面:mentioning
confidence: 99%